Profile and quality of life of children with dual sensory impairment or deafblindness in visually impaired special centres - Rokiah Omar,; Wee, Siew Peng; Wan Syafira Ishak,; Nur Zakiah Mohd Saat,; Victor Feizal Knight, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Coping with dual sensory impairment or deafblindness can be a challenging task for an individual and for the caregiver. Currently limited information is available hence the objective of this study is to determine the profile and quality of life for children with dual sensory impairment or deafblindness. It is hoped that with this information, better rehabilitation programs can be designed for children with deafblindness in Malaysia. A purposive sampling method was adopted. Children with dual sensory impairment were invited to participate in the study. Demographic and hearing loss information was extracted from the children’s medical records. Face to face interviews with parents were conducted using the SF-36 quality of life questionnaire. Vision assessment comprising visual acuity, refraction, cover test, external ocular examination and children’s behaviour observations was conducted. Four children were identified consistent with the based on sample size calculation and who fulfilled the dual sensory impairment criteria out of the 44 children screened. The mean age was 9.3 ± 2.9 years. A majority of the children were of Indian ethnicity. The category of deafblindness seen was congenital deafblindness with rubella as the main cause. All the children were premature babies but had a normal birth weight. The hearing profile showed the majority of them had bilateral profound hearing loss with the mean pure tone average ranging between 50 dBHL and 120 dBHL. The main type of hearing problem was sensorineural and the majority of children owned hearing aids. The visual profile of the deafblindness children revealed either light perception (LP) and categorised as blind or low to moderate myopia. A majority had esotropia. All the children used braille as a visual aids and children with residual vision used closed circuit television (CCTV). Tactile methods were the main means for communication and majority of the children used a white cane. Behaviour and external observation assessments concurred with the hearing and vision impairment manifested. Quality of life in these subjects was lower in 7 out of 8 SF-36 dimensions as compared to normative values. Congenital deafblindness was the main category found among the children in this study and they had profound vision and hearing losses. Tactile methods are the main means of communication for these children. Their quality of life was affected and introducing deafblindness rehabilitation, which includes a combination of hearing and low vision rehabilitation, will be able to assist them in coping with their daily activities.